Subclinical penile human papillomavirus infection and dysplasia in consorts of women with cervical neoplasia. Issue 2 (April 1988) - Campion, M J; McCance, D J; Mitchell, H S; Jenkins, D; Singer, A; Oriel, J D
Abstract : Fifty men whose sexual partners were 50 women with histologically proved cervical intraepithelial neoplasia (CIN) grade III (severe dysplasia or carcinoma in situ) were studied. A further 25 men whose current regular sexual partners were 25 women with chlamydial cervicitis were recruited as controls. If either of the partners in either group had genital condylomata acuminata or a known history of similar lesions, the couple was excluded from the study. Abnormal penile epithelium, which was detected by colposcopy after application of 5% acetic acid to the penile skin, was reported in 25 men in the study group compared with three in the control group. Histologically proved subclinical penile infection with human papillomavirus (HPV) was present in 23 men in the study group compared with three in the control group (p less than 0.01). Of the 50 men in the study group, four had histologically proved severe penile dysplasia or carcinoma in situ with evidence of HPV infection, the disease being subclinical in each case and diagnosed on histology of a specimen obtained by colposcopically directed biopsy. HPV DNA was detected on filter hybridisation of penile scrapes from 15 of the 23 men in the study group with histologically proved penile HPV infection, HPV16 DNA being detected in 10 of them. HPV DNA was detected on DNA-DNA hybridisation of biopsy material in seven of 18 men with histologically proved penile HPV infection. Five of these biopsy specimens were positive for HPV16 DNA. Only one man in the control group had HPV DNA detected in a penile scrape. This patient had histologically proved subclinical penile HPV infection. Such lesions may represent an important male reservoir of HPV types implicated in genital squamous carcinogenesis in both sexes.